Terjadinya Force Majeure Dalam Penyimpanan Minuta Akta Notaris - Prawira, Ida Bagus Putra; Setiabudhi, Ketut Rai; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023), 2023)
This study aims to be able to provide an understanding related to the position of notary deed minuta storage in the event of force majeure and efforts to prevent damage to notary deed minuta caused by force majeure. The writer's method of writing uses normative law departing from the void of norms. The research study of the vacuum of this norm is due to the non-regulation of damage or loss to the storage of minutes of deeds by a Notary which is an obligation in carrying out his position. This research contains primary legal sources that examine the Notary Office Act and secondary legal sources by reviewing several scientific journal literature. Through this research, using the approach refers to laws and regulations regarding the issue of depositing minuta deed referring to the Notary Office Law. The results of the author's research show that the Notary Office Law does not specifically regulate the electronic storage of minutes of deeds. Juridically, safeguarding the minuta deed is not stated in the Notary Office Law and only states that the storage is part of the Notary's protocol. Force majeure is a situation that cannot be predicted by humans, let alone natural disasters. The urgency of updating for the storage of minutes of deeds that are protected from coercive circumstances or beyond human control force majeure is by making electronic fillings with the concept of Cyber Notary.